The Clinical Effect of Oral Vitamin D2 Supplementation on Psoriasis: A Double-Blind, Randomized, Placebo-Controlled Study - Wareeporn Disphanurat; Wongsiya Viarasilpa; Panlop Chakkavittumrong; Padcha Pongcharoen (Hindawi Limited, 2019)
Background. There are limited randomized controlled trials of oral vitamin D supplementation in psoriasis, especially in Asia, and the results are inconclusive. Objective. To investigate the clinical effect of oral vitamin D supplementation on psoriasis. Methods. Patients with psoriasis were randomized to receive vitamin D2 60,000 IU or similar-looking placebo pills once every 2 weeks for 6 months. The primary outcome was improvement of the Psoriasis Area and Severity Index (PASI) score at 3 and 6 months after treatment. Serum levels of 25(OH)D, calcium, phosphate, parathyroid hormone, and C-reactive protein and adverse events were monitored. The chi-square test, Fisher's exact test, Student's t-test, and Spearman's correlation analysis were used in statistical analysis. Results. Of 50 subjects screened, 45 were eligible and randomized to the oral vitamin D2 group (n=23) or placebo group (n=22). At enrollment, the mean PASI score was 4.45, and 26.7% of patients had vitamin D deficiency. At 3 months, the oral vitamin D2 group had significantly higher PASI improvement than the placebo group (mean PASI improvement: 1.43 versus [vs.] -0.33, p-value=0.034; mean %PASI improvement: 34.21% vs. -1.85%, p-value=0.039). The mean serum 25(OH)D level was significantly higher in the oral vitamin D group than in the placebo group (27.4 vs. 22.4 ng/mL, p-value=0.029). Serum 25(OH)D concentrations were significantly inversely correlated with PASI scores at the 6-month follow-up. No major adverse event was observed overall. Conclusion. Oral vitamin D2 supplementation in patients with psoriasis increased the serum vitamin D level and significantly improved the treatment outcome without increasing adverse events. Trial Registration. This trial is registered with Thai Clinical Trials Registry TCTR20180613001.